THE ROLE OF THE TOURISM AWARE GROUP (POKDARWIS) IN THE DEVELOPMENT OF THE KAMPUNG MELAYU SUNGAI SUNGAI MEMPURA TOURISM VILLAGE, SIAK DISTRICT - Nadatul Mafella; Ikhwani Ratna (Yayasan Wayan Marwan Pulungan, 2024)
This research was carried out in Sungai Mempura Village, Siak Regency. This research aims to determine the role of the Tourism Awareness Group (Pokdarwis) in developing tourist villages in Sungai Mempura Village, Siak Regency. The type of research used is descriptive qualitative where descriptive data from answers from research informants describes the phenomena found in the field. The data collection techniques used included observation, interviews, and documentation with informants, the Head of Sungai Mempura Village, the Tourism Awareness Group, Sungai Mempura Village, as well as the community and tourists. Based on the results of research on the development of the Kampung Melayu Sungai Mempura tourist village using the indicators of Attraction, Accessibilities, Amenities, and Ancillary Services, the following results were obtained: The Kampung Melayu Sungai Mempura tourist village has several attractive attractions for people with diverse potential. The natural beauty is still preserved, with good natural potential and a very beautiful environment, and is the center of the Greater Malay Kingdom, commitment to preserving culture is the main magnet. By referring to several indicators used in this research, namely Attraction, Accessibilities, Amenities, and Ancillary Services in the development of the Kampung Melayu Sungai Mempura Tourism Village, it looks quite optimal. However, there are still inhibiting factors seen from several indicators of Accessibility (Accessibility), Amenities (supporting facilities) Ancillary Services (Supporting Services), namely inadequate infrastructure, facilities and infrastructure that are not yet optimal, self-help allocation of funds, and limited human resources.